The Juridical Analysis between Collective Labor Agreements between Employers and Trade Unions/ Labor Unions in the Company - Jaminuddin Marbun (Budapest International Research and Critics University, 2020)
Both Employers and Trade Unions / Labor unions and workers/laborers always want high productivity and the welfare of workers/laborers and their families. This desire can be achieved if employers and trade unions/labor unions as well as workers/laborers are fostered a harmonious working relationship at the company. To create a harmonious working relationship between employers and trade unions/labor unions and with workers/laborers, one of them needs to set working requirements in the company. The Manpower laws does not regulate the working requirements in the company and only regulates work norms in general. The Manpower laws gives employers and trade unions the freedom to enter into an agreement or consensus known as the Collective Labor Agreement, which contains not only the working requirements but it also includes the work norms, and should not conflict with statutory regulations. The Collective Labor Agreement which involves employers and trade unions/labor unions whose contents govern the working requirements and work norms is to explain the rights and obligations of employers and trade unions/labor unions and workers/laborers which constitute the Acts for employers and trade unions/labor unions and workers/laborers and their implementation is overseen by the Office which is responsible for manpower affairs.